2020
DOI: 10.1002/lary.28728
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Sentinel Lymph Node Biopsy for Oral Cancer: A Systematic Review and Meta‐Analysis

Abstract: Objective We assessed the diagnostic accuracy of sentinel lymph node biopsy (SLNB) for detecting neck nodal metastasis in early oral squamous cell carcinoma (OSCC) as an alternative to elective neck dissection. Study Design A systematic search for relevant literature was conducted in the PubMed, SCOPUS, Embase, Web of Science, and Cochrane databases. Methods Two reviewers individually searched the five databases up to November 2019. For studies that met inclusion criteria, data on patient diagnoses were pooled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 109 publications
2
33
1
2
Order By: Relevance
“…38 Recent high-quality meta-analysis endorsed the diagnostic accuracy (in terms of sensitivity and specificity) of SLNB in detecting occult cervical metastasis in patients with cN0 oral cavity cancers. 39 This conclusion was also reinforced in another meta-analysis in patients with only cN0 tongue carcinoma. 38 Additionally, it should be noted that the NCCN guidelines for head and neck cancers highlight SLNB as one of the valuable tools in predicting cervical metastatic disease and subsequently informing the decision of undertaking END in patients with early-stage cT1/T2N0 oral cavity cancers.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…38 Recent high-quality meta-analysis endorsed the diagnostic accuracy (in terms of sensitivity and specificity) of SLNB in detecting occult cervical metastasis in patients with cN0 oral cavity cancers. 39 This conclusion was also reinforced in another meta-analysis in patients with only cN0 tongue carcinoma. 38 Additionally, it should be noted that the NCCN guidelines for head and neck cancers highlight SLNB as one of the valuable tools in predicting cervical metastatic disease and subsequently informing the decision of undertaking END in patients with early-stage cT1/T2N0 oral cavity cancers.…”
Section: Discussionmentioning
confidence: 78%
“…Indeed, SLNB can favourably improve cosmetic outcomes, reduce unnecessary surgery‐associated morbidities and circumvent needless invasive neck dissections 38 . Recent high‐quality meta‐analysis endorsed the diagnostic accuracy (in terms of sensitivity and specificity) of SLNB in detecting occult cervical metastasis in patients with cN0 oral cavity cancers 39 . This conclusion was also reinforced in another meta‐analysis in patients with only cN0 tongue carcinoma 38 .…”
Section: Discussionmentioning
confidence: 99%
“…The area under the SROC curve was 0.851, suggesting acceptable diagnostic accuracy (Figure 2). 22 The correlation between sensitivity and the false‐positive rate was 0.197, indicating the absence of heterogeneity. The sensitivity, specificity, and negative predictive value were 0.8925 ([0.8232–0.9368], I 2 = 55.4%), 0.6884 ([0.6311–0.7404], I 2 = 87.4%), and 0.9802 ([0.9631–0.9894], I 2 = 68.2%), respectively.…”
Section: Diagnostic Accuracy Of Iclnm For Predicting Cclnmmentioning
confidence: 97%
“…Considerable validation studies have demonstrated high intraoperative detection rates (more than 98%) of the sentinel node in oral cancer 13–15 . Moreover, SLNB has exhibited powerful sensitivities ranging from 71.4% to 95% and excellent specificity according to the two latest prospective trials and several diagnostic meta‐analyses 14–18 . In this context, SLNB has been incorporated into the National Comprehensive Cancer Network (NCCN) guidelines for stage I to II SCC of the oral cavity 19 .…”
Section: Introductionmentioning
confidence: 99%